Social Construction of Fisherman’s Community for Maintaining Local Wisdom: A Case Study of Karangjaladri Village - Arie Surya Gutama; Eva Nuriyah Hidayat; Agus Taryana (Komunitas, 2026)
The local wisdom of coastal communities is reflected in the practice of managing marine resources that have been passed down from generation to generation. One form is the fishermen's community which functions as a social forum for fishermen in maintaining traditions and regulating the use of natural resources. However, the development of the era and social dynamics pose challenges and demand adaptation in preserving the values of local wisdom so that an understanding is needed for the fishermen's community to maintain these values. This study aims to analyze the social construction of the fishermen's community in maintaining local wisdom in Karangjaladri Village using the theory of social construction by Berger and Luckmann which includes externalization, objectivation, and internalization. With a qualitative approach and descriptive-explanatory methods, data were obtained through observation, interviews, and documentation. This research was conducted from January 2024 to September 2024 and involved three key informants, namely members of coastal communities who work as fishermen’s , community leaders, representatives of village governments, and other related parties. The results of the study indicate that the fishermen's community forms and maintains local wisdom values through social practices such as cooperation, customary-based fishing area division, and value regeneration through the inheritance of knowledge to the younger generation. In addition, the fishermen's community can adapt to change by strengthening the role of the community in facing the challenges of modernization. This study confirms that social interactions in the fishermen's community form a social reality that is oriented towards preserving local wisdom. The implication is that coastal management policies need to consider the role of fishermen's communities as key figures in maintaining ecological and social balance in coastal areas. Limitations in this study include local wisdom based on the research area, residents in coastal areas, community leaders, and other communities on the coast.